Pengembangan Aplikasi Absensi Siswa Berbasis Web Menggunakan Metode Agile Pada Smk Techno Media - Rafly Putra Afandi; Suliwa Yudha Adinata; Daril Insan Kamil; Wasis Haryono (Jurnal Cakrawala Informasi, 2025)
SMK Techno Media still uses a manual attendance system that is inefficient and prone to errors. This study designs a web-based student attendance application with the Agile method to present a more structured and adaptive solution. Data was obtained from observations, interviews, and literature studies, then continued with a gradual system development process. The test results show that the application is able to accelerate attendance recording and recapitulation, present data in real-time, and run according to function based on the Black Box test. The system is considered effective and feasible to be implemented in other schools facing similar obstacles.